Motivasi Siswi Dalam Mengikuti Kegiatan Rohis di MTsN 1 Gayo Lues - Zahrah, Anita; Nurbayani, Nurbayani; Saiful, Saiful (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to: (1) Find out how motivated female students are in participating in spiritual activities at MTsN 1 Gayo Lues. (2) Knowing the teacher's efforts to increase female students' motivation in participating in spiritual activities. (3) Knowing what factors are successful and inhibiting spiritual activities. This study uses a qualitative method. Data was collected from observations, interviews and documentation. The results of this research were that MTsN 1 Gayo Lues female students participated in spiritual activities without any coercion. The MTsN 1 Gayo Lues teacher council has made various efforts, namely looking for spiritual teaching staff who do not fail in technology and are up to date so that the material provided is interesting and provides evaluation. Factors for the success of spiritual activities at MTsN 1 Gayo Lues, namely: supervision from teachers, interesting discussion material, up to date teaching staff, giving praise and warnings to female students. The inhibiting factors for spiritual activities are: there are some female students who are lazy about participating in spiritual activities, but to overcome this the teacher continues to try to reprimand and advise the female students until the students are motivated to participate in spiritual activities, the distance between the students' homes and school.